The Effect of Early Life Exposure to Triclosan on Thyroid Follicles and Hormone Levels in Zebrafish - Tang, Ning; Fan, Pianpian; Chen, Li; Yu, Xiaogang; Wang, Wenjuan; Wang, Weiye; Ouyang, Fengxiu (Frontiers in Endocrinology, 2022)
Triclosan (TCS) is an antimicrobial chemical widely used in personal care products. Most of the TCS component is discharged and enters the aquatic ecosystem after usage. TCS has a similar structure as thyroid hormones that are synthesized by thyroid follicular epithelial cells, thus TCS has a potential endocrine disrupting effect. It is still not clear how the different levels of the environmental TCS would affect the early development in vivo. This stud examines the effects of TCS on thyroid hormone secretion and the early development of zebrafish. The fertilized zebrafish eggs were exposed to TCS at 0 (control), 3, 30, 100, 300 and 900 ng/mL, and the hatching rate and the larvae mortality were inspected within the first 14 days. The total triiodothyronine (TT3), total thyroxine (TT4), free triiodothyronine (FT3), and free thyroxine (FT4) were measured at 7, 14 and 120 days post fertilization (dpf). The histopathological examinations of thyroid follicles were conducted at 120 dpf. TCS exposure at 30-300 ng/mL reduced the hatching rate of larvae to 34.5 % to 28.2 % in the first 48 hours and 93.8.7 % to 86.8 % at 72 hours =. Extremely high TCS exposure (900 ng/ml) strongly inhibited the hatching rate, and all the larvae died within one day. Exposure to TCS from 3 to 300 ng/mL reduced the thyroid hormones production. The mean TT3 and FT3 levels of zebrafish decreased in 300 ng/mL TCS at 14 dpf(300 ng/mL TCS versus control: TT3, 0.19 ± 0.08 vs. 0.39 ± 0.06; FT3, 19.21 ± 3.13 vs. 28.53 ± 1.98 pg/mg), and the FT4 decreased at 120 dpf(0.09 ± 0.04 vs. 0.20 ± 0.14 pg/mg). At 120 dpf, in the 300 ng/mL TCS exposure group, the nuclear area and the height of thyroid follicular epithelial cells became greater, and the follicle cell layer got thicker. This happened along with follicle hyperplasia, nuclear hypertrophy, and angiogenesis in thyroid. Our study demonstrated that early life exposure to high TCS levels reduce the rate and speed of embryos hatching, and induces the histopathological change of thyroid follicle, and decreases the TT3, FT3 and FT4 production in zebrafish.